The Effect of Jarimatics-Based Drill Method on Multiplication Operation Skills of Third Grade Elementary School Students - Nurhidaya Sangeran; Suarti Djafar; Irman Syarif (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: This research is motivated by the learning of mathematics in class III elementary school still using the lecture method and the lack of use of media and methods in learning. The jarimatika-based drill method is expected to be a solution to the problems found. Aim: The objectives of this study are: 1) To determine the multiplication operation ability of class III students of elementary school before using the jarimatika-based drill method, 2) To determine the multiplication operation ability of class III students of elementary school after using the jarimatika-based drill method, 3) To determine the effect of the jarimatika-based drill method on the multiplication operation ability of class III students of elementary school. Method: This type of research is an experiment with a Pre-Experimental One Group Pretest-Posttest design. The sample of this study was 11 class III students. The study was conducted in 8 meetings. Data collection techniques are tests, observations and documentation. Data analysis techniques in this study are validity tests, reliability tests, descriptive statistics, normality tests, homogeneity tests, hypothesis tests and N-gain tests. Result and Discussions: The results of the study showed that: 1) The average pretest score was 56.45, 2) The average posttest score was 76.64, 3) The results of the Paired Sample T-test in this study have an influence of the jarimatika-based drill method on students' multiplication operation abilities. It can be seen from the analysis results that there is a significant difference between the pretest and posttest scores, namely (t(10) = -7.971, p < 0.000, with a significance value of 0.000 < 0.05.